The Effect of Benefits, Service Quality, Ease of Use on the Attractiveness and Satisfaction of Dana's E-Wallet Consumers - Hani Aprilia Sari; Minto Waluyo (Politeknik Negeri Bengkalis, 2022)
The COVID-19 pandemic has changed all community activities that should have been carried out directly (offline) into online activities, including transaction activities. The change in the pattern of online transactions has turned into an e-wallet (e-wallet). This study has a purpose, namely to determine the effect of variable benefits, service quality, and ease of use on the attractiveness and satisfaction of DANA E-Wallet consumers. This research is a quantitative research conducted at the e-wallet company PT Elang Sejahtera Mandiri, namely DANA. The focus of this research is on users of the DA-NA application. The population of this study was conducted on DANA e-wallet users in Indonesia using sampling data. In this study using as many as 20 indicators. This research is included in cross sectional research, namely research that is used to determine the comparative relationship of several subjects who want to be studied with a sample of respondents through one data collection. The results of the study of the effect of the variables of benefit, service quality, and ease of use on the attractiveness and satisfaction of DANA E-Wallet consumers showed that the benefits and service quality had a positive effect on the attractiveness of using DANA e-wallet. Meanwhile, user convenience cannot be proven in this study because the convenience variable is excluded from the research model